Dislocation Distances of Labor Settlements Positions in the Komi ASSR, Arkhangelsk and Vologda Regions in 1941–1942 - N. М. Ignatova (Историко-географический журнал)
The article analyzes data on the location of labor settlements based on deployment tables. The deployment tables refer to departmental reporting documentation of the NKVD of the USSR. The information reflects the situation for the period 1941-42, since the data for the Arkhangelsk region are given as of November 1941, for the Komi ASSR as of January 1, 1942, and for the Vologda region as of December 31, 1942. The requirements for the position of labor settlements and the features of their organization are considered. A calculation of the average distances from labor settlements to the railway track, the district commandant’s office and the regions’ administrative center is given. Analyzing the distances from labor settlements to transport routes, district and administrative centers allows assessing remoteness of settlements from railway transport and populated areas. The Komi ASSR, Arkhangelsk and Vologda regions in 1929–1936 were administratively united as part of the Northern Krai, so the organization in the early 1930s of settlements for special settlers – “former kulaks,” renamed in labor settlements in 1933, proceeded according to general plans, so it seems relevant to assess the situation for the three regions as a whole.